Characterization of T cells and cytokines in the aqueous humour (AH) in patients with Fuchs' heterochromic cyclitis (FHC) and idiopathic anterior uveitis (IAU) - Muhaya, M (Blackwell Science Inc, 1998)
FHC and IAU are two forms of anterior uveitis which are localized to the eyes with no evidence of systemic involvement. However, FHC has distinct clinical features and differs from IAU in that the inflammation is low grade, steroid non-responsive, and has a less aggressive clinical course. To try to dissect the mechanism for this difference the phenotypes of the cells in the AH and blood (PB) and the cytokines present in the AH in patients with FHC and IAU were compared. Three-colour flow cytometry was performed on the cells isolated from the AH and PB. Percentage of cells bearing the following markers were determined: CD3, CD4, CD8, CD4/CD25, CD8/CD25, CD19 and CD14. The cytokines IL-4, IL-10, IL-12 and interferon-gamma (IFN-γ) were assayed by ELISA. In both groups T cell numbers were higher in the AH than PB, although the distribution of T cell subsets in PB was similar. In the AH, CD8(+) T cell numbers were higher in FHC than in IAU (P = 0·003), whilst CD4(+) numbers were higher in IAU than FHC (P = 0·01). AH cytokine profiles were different in the two groups: IFN-γ levels were higher and IL-12 levels lower in the FHC group than IAU (P = 0·02), whilst IL-10 levels tended to be higher in the FHC group (P = 0·5). We suggest that different local mechanisms governing the balance of T cell/cytokine-mediated inflammation in the anterior segment may underlie clinical differences such as chronicity and response to steroids in these disorders.